Water Transfer Printing Enhanced by Water‐Induced Pattern Expansion: Toward Large‐Area 3D Electronics. Issue 4 (7th February 2019) - Le Borgne, Brice; Liu, Siyi; Morvan, Xavier; Crand, Samuel; Sporea, Radu Alexandru; Lu, Nanshu; Harnois, Maxime
Abstract: Perfectly wrapping planar electronics to complex 3D surfaces represents a major challenge in the manufacture of conformable electronics. Intuitively, thinner electronics are easier to conform to curved surfaces but they usually require a supporting substrate for handling. The water transfer printing (WTP) technology utilizes water surface tension to keep ultrathin electronics floating flat without supporting substrate, enabling their conformal transfer on 3D surfaces through a dipping process. In many cases, however, the size of the microfabricated electronics is much smaller than the target 3D surface. This work proposes that such mismatch in size can be overcome by leveraging stretchable electronics in WTP. Stretchable electronics are compliant to in‐plane stretch induced by water surface tension, hence can first self‐expand in water and then be transferred onto 3D objects. Uniaxial and biaxial expansion ranging from 41% to 166% has been achieved without any externally applied tension. The results demonstrate that expansion‐enhanced WTP is a promising fabrication process for conformable electronics on large 3D surfaces. Abstract : This work presents the control of the water‐induced pattern expansion of water transfer printing to fabricate large‐area 3D conformable electronics from small‐scale fabrication . By introducing proper guides, the water‐assisted pattern expansion can be well controlled to expand uniaxially or biaxially up to 166%. The presented technique can be combined with stretchable electronics for improved conformability.